The Potential of Endophytic Bacteria as the Biocontrol Agents of Fusarium proliferatum - Ernia, Rima; Mubarik, Nisa Rachmania; Sudirman, Lisdar Idwan (Makara Journal of Science, 2023)
Fusarium proliferatum decreases the productivity of shallot (Allium cepa L.). Endophytic bacteria are potential biocontrol agents in controlling the growth of F. proliferatum. This study aimed to select and characterize endophytic bacteria producing bioactive compounds that inhibit the growth of F. proliferatum. The endophytic bacteria used were isolated from the roots, stems, leaves, and soil of shallot plants from healthy and diseased shallot farming fields. The endophytic bacteria were selected using the dual culture method and extracted using ethyl acetate solvent. The results of the 16S rRNA identification suggested that isolate ABP5.2 is similar to Pseudomonas aeruginosa, while isolates BBP5.2 and DBP4.1 are similar to Myroides profundi. Isolate BBP5.2 was found to have the highest ability (68.15%) to inhibit the growth of F. proliferatum by using its antifungal compounds through a direct mechanism. In addition, the results of the Gas Chromatography-Mass Spectrophotometry analysis suggested that the compounds produced by the crude extracts of BBP5.2 isolate are hexadecanoic acid, 9-octadecenoic acid, linoleic acid, and piperine.